Business Development Strategy for Revenue Growth at Square Coffee - Mulyani Mulyani; Ilham Illahi; Khadijah Nurani; Yenti Astarie Dewi (INCOME: Innovation of Economics and Management, 2026)
Purpose – This study aims to analyze the business development strategy of Square Coffee Payakumbuh to improve business income by identifying the internal and external strategic factors influencing its competitiveness. As a Micro, Small, and Medium Enterprise (MSME) in the coffee shop industry, Square Coffee Payakumbuh faces challenges related to fluctuating income, customer loyalty, and increasing market competition despite implementing various promotional activities. Design/methodology/approach – A qualitative descriptive approach was employed using SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. Data were collected through observations and semi-structured interviews with the business owner, employees, and customers. Internal and external strategic factors were evaluated using the IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) matrices before being integrated into the SWOT matrix to formulate business development strategies. Finding/Results – The IFAS score of 2.65 indicates that Square Coffee Payakumbuh possesses relatively strong internal capabilities that outweigh its weaknesses, while the EFAS score of 2.75 suggests that external opportunities are more dominant than potential threats. The SWOT matrix places the business in the Strength–Opportunity (SO) quadrant with the highest strategic score (4.05), indicating an aggressive growth position. The recommended strategy emphasizes leveraging product diversity, café ambience, competitive pricing, and service quality to capitalize on expanding coffee consumption trends, digital marketing channels, and strategic collaborations. Originality/Value – This study provides a context-specific SWOT strategy based on IFAS–EFAS analysis for a local coffee shop. The findings offer practical strategic guidance for similar MSMEs operating in competitive local markets.